(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents the results of the determination of pharmacologically active secondary metabolites of the resin of the plant Ferula tadshikorum L. using high performance liquid chromatography (HPLC). The chemical composition of the volatile fractions of the hexane extract of the resin of the roots of the plant Ferula tadshikorum, determined by the GX-MS method, was studied. During the study, a hexane fraction was obtained from the resin, from which 5 main components were isolated.